Йорданські свічки – «Трійці» - Зозуля, Н. (Народна творчість та етнографія, 2009)
In the research Jordanian candles – «trinities» are considered as the main attribute of Epiphany. There is given the information of different ethnologists about the use of the Jordanian candles during celebration of Epiphany.